The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/pcn.12029
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Treatment Research to Improve Cognition in Schizophrenia Consensus Cognitive Battery: Validation of the Japanese version

Abstract: Aim: This preliminary study was performed to test the reliability and validity of the Measurement and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) Consensus Cognitive Battery (MCCB), developed by the National Institute of Mental Health MATRICS initiative, as an assessment tool in a Japanese-language version (MCCB-J). Methods:The subjects for the present study were 37 patients with schizophrenia. Each subject gave written informed consent to participate in the research. In order to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…UPSA-B and MCCB. In fact, cognitive function evaluated by the BACS used here has been shown to correlate with performance on the MCCB Japanese version (Kaneda et al, 2013). …”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…UPSA-B and MCCB. In fact, cognitive function evaluated by the BACS used here has been shown to correlate with performance on the MCCB Japanese version (Kaneda et al, 2013). …”
Section: Discussionmentioning
confidence: 80%
“…Cognitive assessment was conducted by the Japanese version of the Brief Assessment of Cognition in Schizophrenia (BACS) (Kaneda et al, 2013), based on the original version (Keefe et al, 2004). The cognitive domains included in the BACS are verbal memory, working memory, motor speed, verbal fluency, attention, and executive function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCCB has good test-retest reliability, practicability, and tolerability,40 and it is reported that the Japanese version of the MCCB has good psychometric properties and validity 55. It was reported that the Japanese version had high internal consistency (Cronbach coefficient alpha was 0.72) 55. In the present study, data were collected using the Japanese version by clinical psychologists who were well trained for the use of it.…”
Section: Methodsmentioning
confidence: 85%
“…The MCCB composite score gives equal weighting to each of the seven cognitive domains. The MCCB has good test-retest reliability, practicability, and tolerability,40 and it is reported that the Japanese version of the MCCB has good psychometric properties and validity 55. It was reported that the Japanese version had high internal consistency (Cronbach coefficient alpha was 0.72) 55.…”
Section: Methodsmentioning
confidence: 99%